Implementation The Act Against The Material Law In Act No. 31 of 1999 jo Act No. 20 of 2001 Concerning of Corruption Linked With Constitutional Court's Decision No. 003 / PUU / IV / 2006 - Danceu Danceu (Jurnal Daulat Hukum, 2018)
The problem in this research are: (1) How is the location of the nature of the unlawful material law in Act No. 31 of 1999 Jo Act No. 20 of 2001 on the Corruption linked with Constitutional Court Decision No. 003 / PUU / IV / 2006?; (2) What is the nature of policy implementation against the material law in Corruption Act after the decision of the Constitutional Court Number 003 / PUU / IV / 2006? Research methods is descriptive analytical by using sociological juridical approach. The results of the study author shows that the nature of the unlawful material in Act No. 31 of 1999 Jo Act No. 20 of 2001 on the Corruption linked with Constitutional Court Decision No. 003 / PUU / IV / 2006 of the nature of the unlawful material, used as means the eradication of corruption in the Act No. 31 1999 Jo Act No. 20 of 21 declared non-binding with legal certainty (in violation of Article 28 D Constitution 1845), implementation of a policy nature against the law material in Act of Corruption after the decision of the Constitutional Court Number 003 / PUU / IV / 2006 by the legislative arrangements do not exist anymore in the Law on Corruption Eradication.Keywords: Personality Against Material Law; Corruption; Constitutional Court Decision.